Description of Acute Respiratory Infection in Children at Sukorame Health Centre, Kediri, East Java 2021 - Jami Atun Ummah (Ficco Public Health Journal, 2024)
Background: Acute respiratory infection is an event that causes high levels of death and morbidity worldwide. Each year, the death rate due to acute respiratory infection reaches 4 million people and 98% of these deaths are due to lower respiratory tract infections. This study describes the distribution of acute respiratory infection incidents among toddlers in the Sukorame Health Centre in 2021. Methods: This is a descriptive observational study. Located at Sukorame Health Centre, Kediri City. Data collection took place over three weeks, from 10 to 29 January 2022. Results: Age group less than 1 year, the highest number of cases occurred in cases of non-infectious cough, with a total of 459 cases, and in cases of infection, with 39 cases. The gender with the highest number of cases was men diagnosed with cough rather than pneumonia, with a total of 910 cases, and men also had the highest number of cases diagnosed with pneumonia, with a total of 83 cases. In women, 749 cases of non-infectious cough were diagnosed and 61 cases of infection. The areas with the highest number of cases are Bujel subdistrict (387 cases) and Bandar Lor subdistrict (333 cases). Conclusion: Infection at the age of 1-5 years is greater than at age <1 year. Both men and women have the same percentage of infections. The highest infection rate is in Bujel sub-district.